Peningkatan Kesadaran Keamanan Informasi Siswa SMK Telkom Purwokerto Melalui Pelatihan Footprinting dan Reconnaissance - Wahyu Adi Prabowo; Rifki Adhitama; Auliya Burhanuddin; Paradise Paradise; Khusnul Fauziah; Aufa Salsabila Nahrowi (LPPM IT Telkom Purwokerto, 2024)
The community service activity aims to delve into the concept of footprinting and reconnaissance in cybersecurity focusing on students at SMK Telkom Purwokerto. Guided by lecturers and students, the activity aims to enhance participants' understanding of vital early information analysis and gathering techniques in the realm of cybersecurity. Implementation methods include online learning and direct practical sessions in the classroom, enabling participants to implement these concepts. The training benefits encompass an improved understanding of system security threats, the development of technical analysis skills, and the ability to implement better protective measures. The results demonstrate active participation and an enhanced understanding of the importance of footprinting and reconnaissance in managing information security risks among the participants. There was a 90% increase in awareness after the participants underwent the training, indicating a positive impact of this activity on students' comprehension of information security. Therefore, this activity not only supports the tridharma of higher education but also strengthens the relationship between the Telkom Purwokerto Institute of Technology and the community in enhancing local cybersecurity.